Use of Acellular Biologic Matrix Envelope for Cardiac Implantable Electronic Device Placement to Correct Migration into Submuscular Breast Implant Pocket - Peyton Terry; Kenneth Bilchick; Chris A. Campbell (Archives of Plastic Surgery, 2023)
Breast implants whether used for cosmetic or reconstructive purposes can be placed in pockets either above or below the pectoralis major muscle, depending on clinical circumstances such as subcutaneous tissue volume, history of radiation, and patient preference. Likewise, cardiac implantable electronic devices (CIEDs) can be placed above or below the pectoralis major muscle. When a patient has both devices, knowledge of the pocket location is important for procedural planning and for durability of device placement and performance. Here, we report a patient who previously failed subcutaneous CIED placement due to incision manipulation with prior threatened device exposure requiring plane change to subpectoral pocket. Her course was complicated by submuscular migration of the CIED into her breast implant periprosthetic pocket. With subcutaneous plane change being inadvisable due to patient noncompliance, soft tissue support of subpectoral CIED placement with an acellular biologic matrix (ABM) was performed. Similar to soft tissue support used for breast implants, submuscular CIED neo-pocket creation with ABM was performed with durable CIED device positioning confirmed at 9 months postprocedure.